Seafloor Methane Seepage Related to Salt Diapirism in the Northwestern Part of the German North Sea - Römer, Miriam; Blumenberg, Martin; Heeschen, Katja; Schloemer, Stefan; Müller, Hendrik; Müller, Simon; Hilgenfeldt, Christian; Barckhausen, Udo; Schwalenberg, Katrin (Frontiers in Earth Science, 2021)
This study focusses on seafloor methane seep sites and their distribution in the northwestern part of the German North Sea. Methane seepage is a common phenomenon along marine shelfs and known to occur in the North Sea, but proof of their existence was lacking in the study area. Using a ship-based multibeam echosounder we detected a minimum of 166 flares that are indicative for free gas releases from the seafloor in the German ´Entenschnabel´ area, which are not related to morphologic expressions at the seafloor. However, a group of small pockmarks was detected lacking water column anomalies but with indications of dissolved fluid release. Spatial analysis revealed that flares were not randomly distributed but show a relation to locations of subsurface salt diapirs. Most flares were found in the vicinity of the salt diapir ‘Berta’. Dissolved methane concentrations of ~ 100 nM in bottom waters were ten times the background value in the ´Entenschnabel´ area (CH4 <10 nM), supporting the finding of enhanced seepage activity in this part of our study area. Furthermore, locations of flares were often related to narrow acoustic blanking and high amplitude reflections in sediment profiler echograms, most prominently observed at location Berta. These signatures are interpreted to result from increased gas concentrations in the sediments. Electromagnetic seabed mapping depicts local sediment conductivity anomalies below a flare cluster at Berta, which can be explained by free gas concentrations up to 2% of total volume. Nine abandoned well sites were included in our mapping campaign, but flare observations were spatially not related to these wells. Naturally seeping methane is presumably transported to the seafloor along sub-vertical faults, which have formed concurrently to the updoming salt. Due to the shallow water depths of 30 to 50 m in the study area, flares were observed to reach close to the sea surface and a slight oversaturation of surface waters in the flare-rich northeastern part of the working area indicates that at least part of the released methane is contributing to the atmospheric inventory.